The Effect Of Pumpkin (Cucurbita moschata D.) And Peel Of Watermelon (Citrullus lanatus) Balance On The Characteristics Of Jam Produced - Kelik Putranto; Dara Berliana Kusuma; Qori Istiqomah (International Journal of Quantitative Research and Modeling, 2023)
Jam is a semi-solid food ingredient made no less than 45 parts by weight of crushed fruit with 55 parts by weight of sugar. The mixture is thickened until it reaches a content of a dissolved solid substance of not less than 65% for all types of jam. The main components or conditions for making jam are pectin, sugar and acid. Pectin requirements for the manufacture of jams are a maximum of 0.75% and a minimum sugar of 55%. Ideal fruits in the manufacture of jam should contain enough pectins and acids to produce jams with appropriate characteristics.Research on the jam characteristics of various yellow pumpkin and watermelon peel balances has been tried with the aim of establishing the right balance. The method used in this study was an experimental method using a Randomized Block Design. The balance treatment of yellow pumpkin and watermelon peel consists of balancesA (100: 0) , B (90 : 10), C (80 : 20), D (70 : 30), E (60 : 40) and F (50 : 50), each treatment is repeated four times. Inter-treatment testing using duncan multiple range test at a real level of 5%.The results showed that the balance of yellow squash and watermelon peels gave a noticeable difference in the effect on the moisture content, vitamin C, total soluble solids, the degree of liking for the color, taste, aroma and consistencyof the jam. The balance of yellow pumpkin and watermelon peel (70:30) produces good jam characteristics, this determination is based on a color favorability level of 4.16 , taste of 4.04 and consistencyof 3.63 out of a maximum value of 5.00 and a total soluble solid of 70.03%.